2022
DOI: 10.1177/03913988221118102
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on intact human umbilical cord Wharton’s jelly as a scaffold for human autologous chondrocyte: In-vitro study

Abstract: Objectives: Placental tissue is an established biomaterial used in many clinical applications. However, its use for tissue engineering purposes has not been fully realized. Though articular cartilage extracellular matrix (ECM)-derived oriented scaffolds for cartilage tissue engineering were developed, resources are a hindrance to its application. In this regard, the present study investigated the feasibility of using intact decellularized human umbilical cord Wharton’s jelly (hUC-WJ) as a new material for chon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The UC-derived WJ scaffold supported cartilaginous attachment, when used with autologous chondrocytes, demonstrating the potential of WJ to be used to regenerate articular cartilage. 25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UC-derived WJ scaffold supported cartilaginous attachment, when used with autologous chondrocytes, demonstrating the potential of WJ to be used to regenerate articular cartilage. 25 …”
Section: Resultsmentioning
confidence: 99%
“…determined that a decellularized human UC-WJ scaffold effectively supports a microenvironment necessary for the attachment of viable chondrocytes. 25 Overall, only a few in vitro studies examined the specific effects of WJ-MSCs on knee OA, and future research should evaluate the immunomodulatory impact of these stem cells on knee OA. Overall, the basic science studies published so far have shown promising results, but further investigations should be conducted looking at additional metrics, such as inflammatory, degenerative, cell death markers to state more conclusively that this biologic therapy can produce beneficial results in patients with knee OA.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In the current framework, the idea, at the base of the current article, is to make an attempt to ameliorate the functionality of the IVD cells embedded in a degenerated disc environment, by exploiting the properties of a specific ECM with high potential in regenerative medicine, namely the decellularized matrix obtained from the umbilical cord Wharton's jelly (DWJ). 11,12 It is indeed well known that DWJ possesses several properties well suitable for tissue repair/ engineering approaches, including biomechanical, immunomodulatory, antibacterial, and biocompatibility features. 13 The human Wharton's jelly, in the last few years, has indeed received an increasing attention due to its potential for regenerative medicine applications as "natural constituent" to produce biomimetic scaffolds.…”
Section: Introductionmentioning
confidence: 99%